Detection of latent tuberculosis infection in BCG vaccinated children - Paluch-Oleś, Jolanta; Magryś, Agnieszka; Kozioł-Montewka, Maria (Polish Journal of Public Health, 2011)
Introduction. Children with tuberculosis represent about 11% of all notified incidences of the disease. Especially young children are at high risk of infection because of the decreased ability of their immunes to combat the pathogens and children 3≤12. In the analyzed group of patients, 127 (81.4%) had negative tests results. Among these, one QFT-IT result was subliminal (0.31UI/ml). Twenty one (13.5%) of the 156 studied children had indeterminate QFT-IT results. The proportion of indeterminate results was the highest in the youngest age group. Conclusions. Our results indicate the low rate of LTBI among the studied children. The infection rate detected with QFT-IT is more likely than identifying with TST owing to small rate of childhood TB in Poland.